Usual food intakes of 2- and 3-year old U.S. children are not consistent with dietary guidelines. Issue 1 (December 2016) - Fox, Mary; Gearan, Elizabeth; Cannon, Judith; Briefel, Ronette; Deming, Denise; Eldridge, Alison; Reidy, Kathleen
Abstract Background The primary purpose of this paper is to assess how well food consumption patterns of young children in the U.S. conform to the 2015Dietary Guidelines for Americans. A secondary purpose is to gain insight into food choices that contribute to over- or under-consumption of key food groups and dietary constituents. Methods The analysis used data from the Feeding Infants and Toddlers Study 2008 (FITS 2008), and a national random sample of 1323 2- and 3-year old U.S. children. Children's usual food intakes were estimated using the National Cancer Institute method and proportions of children whose usual diets did not include recommended amounts of food groups were assessed, as well as the proportions that consumed excess calories from solid fat and added sugars. Leading sources of vegetables, grains, oils, solid fat and added sugars were also examined. Results The prevalence of usual food group intakes that did not meet recommendations was highest for vegetables (91%), whole grains (94%), and oils (>99%). In addition, virtually all children (>99%) had usual intakes of calories from solid fat and added sugars that exceeded the maximum allowance. The mean intake of calories from solid fat and added sugars was almost three times the maximum allowance. Conclusions Given that children's food preferences and habits develop early in life, educating primary caregivers about recommended feeding patterns and how to promote them is critical. Infants and young children will readily accept sweet and salty foods, but the wider variety of foods associated with healthy eating patterns may only be accepted if children have repeated experience with them. There is evidence that some caregivers may overestimate the quality of their children's diets, so specific, practical, and actionable guidance is needed. This advice should include education about children's normal resistance to new foods, strategies for promoting acceptance and not using food to manage behavior. Given that one-third of children under the age of five attend regular child care outside the home, child care centers and family day care homes also have an important role to play in developing healthy food habits and preferences among young children.